DF-Fit: a robust algorithm for detection of crystallographic information in atom probe tomography data - Haley, D; Moody, MP; Bagot, PAJ (University of Oxford, 2018)
Data was acquired via atom probe tomography, and processed using the DF-FIT algorithm, available from apttools.sourceforge.net.